The Effect of Service Quality on Customer Satisfaction at Mie Celor 26 Ilir H.M Syafei Z Palembang - Mifthahul Maula; Esya Alhadi (International Journal of Advanced Research in Social Studies, 2022)
This study aims to determine the effect of service quality on consumer satisfaction at Mie Celor 26 Ilir H.M Syafei Z Palembang. The methodology used in this research is descriptive quantitative. The accidental sampling technique was applied. The participants were consumers at the stall by a total of 100 respondents. Based on the t-test, the value of t-count was higher than t-table (3.860 > 1.984). It means that service quality has a significant effect on consumer satisfaction. While in the calculation of the coefficient of determination, the result obtained was 55%. Cornbach's Alpha value on service quality also showed that it was higher than the crisis value, which was 0.902, and then the variable was declared reliable since exceeded 0.600.